Why a generalized serological screening in early pregnancy for CMV is just not justifiable? - Ana DUMINICA; Corina GICA; Nicolae GICA; Radu BOTEZATU; Gheorghe PELTECU; Anca Marina CIOBANU; Anca Maria PANAITESCU (Romanian Journal of Medical Practice, 2020)
Infections acquired during pregnancy add up to the overall perinatal rate of mortality and morbidity. Because it has the potential to be screened in all pregnant women, infection with cytomegalovirus continues to raise awareness among obstetricians and healthcare providers, given the perinatal complications involved, but also because not all parturient women are equally informed about the impact of the disease. A significant possibility of vertical transmission is attainable if primary infection is acquired in pregnancy, especially in the first trimester, when the risk of developing a congenital neonatal disease is higher. Even so, there are many more steps to be taken into consideration in order to fully understand the consequences of the infection, given the fact that the leading consequence of the congenital disease is the sensorineural hearing loss in the neonates, thus raising an important question: why a generalized serological screening in early pregnancy for CMV is just not justifiable?